Hospitalisation cost analysis on hip fracture in China: a multicentre study among 73 tertiary hospitals. Issue 4 (27th April 2018) - Wang, Yilin; Cui, Haoran; Zhang, Dianying; Zhang, Peixun
Abstract : Objective: To describe and analyse the hospitalisation cost of patients with hip fracture under the influence of various factors and to provide references for Chinese national medical insurance policy. Materials and methods: All data were collected from the Chinese National Medical Data Centre database, which contained the hospitalisation data of 73 tertiary hospitals from 24 provinces. The included patients were first hospitalised with the main diagnosis of femoral neck or intertrochanteric fracture, and were discharged between 1 January 2014 and 31 December 2015. Secondary hospitalisation, multiple trauma or pathologic fracture (except for osteoporotic fracture) patients or patients with missing data were excluded. The impact of various factors on the cost was investigated using analysis of variance and multivariable linear regression analysis. The Gross Domestic Product per capita and average annual disposable income were obtained from the website of the National Bureau of Statistics. Results: 27 205 cases were included in the study. The mean cost of all patients was ¥53 440. 60–69 years age group had a significantly higher cost compared with 80 years and above age group. The mean cost of femoral neck fractures was lower than that of the patients with intertrochanteric fractures; the mean cost of hip replacement was higher than that of internal fixation, which showed a strong effect of the surgical approach to the cost. Patients in low-income provinces spent less than those in high-income provinces, while the gap between high-income and middle-income provinces were relatively small. Conclusion: The hospitalisation cost of hip fracture has become a great burden to the patients' families. The Chinese medical insurance policy may need further consideration of the demographic and economic factors.